Identification of a HERV‐K env surface peptide highly recognized in Rheumatoid Arthritis (RA) patients: a cross‐sectional case–control study. (9th May 2017) - Mameli, G.; Erre, G. L.; Caggiu, E.; Mura, S.; Cossu, D.; Bo, M.; Cadoni, M. L.; Piras, A.; Mundula, N.; Colombo, E.; Buscetta, G.; Passiu, G.; et al.
Summary: Endogenous retroviruses (HERV) are believed to be pathogenic in several autoimmune diseases. Among them, HERV‐K viruses have been reported recently to be involved in the pathogenesis of rheumatoid arthritis (RA). In this study we have explored the role of humoral immune response against HERV‐K as a potential pathogenetic mechanism in RA. Four different peptides from the extracellular portion of the env protein of HERV‐K (env‐su19–37, env‐su109–126, env‐su164–186, env‐su209–226 ) were selected by bioinformatic analysis on the basis of their putative immunogenicity. Indirect enzyme‐linked immunosorbent assay (ELISA) was then carried out to quantify antibodies against those peptides on blood samples of 70 consecutive RA patients and 71 healthy controls (HC). Differences between the two groups were analysed using the Mann–Whitney test. Potential correlations between RA laboratory, clinical descriptors and immunoglobulin (Ig)G levels were explored by bivariate regression analysis. Serum autoantibodies against one of four tested peptides of HERV‐K (env‐su19–37 ) were significantly higher in RA than in HC (19 versus 3%, P = 0·0025). Subgroup analysis showed no association between anti‐HERV‐K peptide humoral response and clinical, serological and clinimetric RA disease descriptors. Serum from RA patients in our series reacted significantly against HERV‐K env‐su19–37 peptide in comparison to the general population suggesting a role for the HERV‐K‐ related, secondary antigenic‐driven immune response in the pathogenesis of RA. Further studies are needed to confirm these results and to explore the role of this HERV‐K surface peptide as a potential therapeutic target. Abstract : We report the novel observation related to the presence of antibodies recognizing a specific epitope of HERV‐K in serum of Rheumatoid Arthritis (RA) patients in comparison to healthy controls. The peptide may be used as a biomarker of disease progression if confirmed in a larger setting of patients.